RIFFATERRE'S SEMIOTIC ANALYSIS OF THE SONG ATUNA TUFULI BY REMI BANDALI - Muhammad Nurfaizi Yuhmansyah; Sitti Wahidah Masnani; Haeruddin Haeruddin; Andi Agussalim; Mujadilah Nur (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Songs are one form of oral literature that has the power to convey messages through language and music. So the analysis of the meaning of the lyrics of the song Atuna Tufuli popularized by Shirine was carried out using Michael Riffaterre's semiotic analysis which focuses on the analysis of poetry (song lyrics). This study aims to find the meaning of the lyrics of the song Atuna Tufuli by describing namely (1) indirectness of expression, (2) heuristic and hermeneutic reading, (3) matrix, and (4) Model and hypogram (intertextual correlation). This study is a descriptive-qualitative type of research with a semiotic approach and the lyrics of the song Atuna Tufuli as its corpus. The design used in this study is a library study (Library Research). The results show that the lyrics of Atuna Tufuli by Remi Bandali utilize indirectness of expression to convey the complex meaning of love. (1) indirectness of expression includes: (a) Displacement of meaning. (b) distortion of meaning. (c) Creation of meaning. (2) Heuristic and Hermeneutic Readings describe the expression of suppressed feelings of love. (3) The matrix of these lyrics can be identified as "the desire of children in conflict areas to have freedom and a normal life". (4) Model and hypogram (intertextual correlation), the model can be various elements that are already known to the listener or reader, such as the theme of the desire to have freedom and a normal life, as well as the call for attention and assistance for children living in conflict and violence, the style of writing lyrics, and expressions of longing that can be found in works of art, literature, and music. The hypogram in the song "Atuna Tufuli" by Remi Bandali lies in the repetition of classical themes that emphasize the desire of children to have a normal childhood and peace, which are often found in ancient Arabic poetry.